Morphofunctional analysis of human pancreatic cancer cell lines in 2- and 3-dimensional cultures - Fuuka Minami (Nature Portfolio, 2021)
Abstract Genetic, transcriptional, and morphological differences have been reported in pancreatic ductal adenocarcinoma (PDAC) cases. We recently found that epithelial or mesenchymal features were enhanced in three-dimensional (3D) cultures compared to two-dimensional (2D) cultures. In this study, we examined the differences in the morphological and functional characteristics of eight PDAC cell lines in 2D and 3D cultures. Most PDAC cells showed similar pleomorphic morphologies in 2D culture. Under 3D culture, PDAC cells with high E-cadherin and low vimentin expression levels (epithelial) formed small round spheres encircled with flat lining cells, whereas those with high vimentin and low E-cadherin expression levels (mesenchymal) formed large grape-like spheres without lining cells and were highly proliferative. In 3D culture, gemcitabine was more effective for the spheres formed by PDAC cells with epithelial features, while abraxane was more effective on those with mesenchymal features. The expression levels of drug transporters were highest PDAC cells with high vimentin expression levels. These findings indicate that PDAC cells possess various levels of epithelial and mesenchymal characteristics. The 3D-culture method is useful for investigating the diversity of PDAC cell lines and may play important roles in the development of personalized early diagnostic methods and anticancer drugs for PDAC.